PENGARUH LATIHAN KERUCUT KE KERUCUT TERHADAP KEMAMPUAN MENGGIRING BOLA PADA SSB CHEVRON U-15 RUMBAI PEKANBARU - Rahmat Hidayat; Slamet Slamet; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The purpose of this study to determine the effect of exercise on the Cone to Cone to dribble the ballat SSB CHEVRON U-15 Rumbai Pekanbaru. In this study, the researchers took the population of 16 players of SSB CHEVRON U-15 Pekanbaru. The sample in this research used total sampling technique which is the full sample of total population. The desing of this study using one group then this research approach to wear one-group pretest-postest desing. The instrument used to collect the data was by Dribbling Ball test, which aimed to improve the ability to dribble the ball. After that, the data is processed statistically, to test the normality with liliefors test at a significant level (0.05). The hypothesis proposed is the effect of exercise on the ability of Cone to Cone in dribbling the ball. Based on the analysis of statistical data, there are flat-rate of pre tests is 21.26 and an average of post test 21,00 then the data normal is with an increase number of 0.99. Based on T test analysis which amounted 9 with tabel T is 1,753, it means t hitung> t table. Thus, there is the influence of exercise of Cone to Cone in dribbling at SSB Chevron Rumbai Pekanbaru.Keywords : Exercise of Cone to Cone, Dribbling the Ball